PENDIDIKAN NILAI-NILAI KEMANUSIAAN DI SMP INSAN TELADAN KALISUREN KABUPATEN BOGOR - Ramadhita, Nurul; Budiaman, Budiaman (Edukasi IPS, 2018)
This research purpose to understand the impact of humanity daily on the lives of students as well and its inhibiting factors. The educational impact of humanitarian values consists of impact on the daily students and impact on the environment in approximately students. Then the inhibiting factors come from foundations, schools, students, and parents. This research was conducted at Insan Teladan junior high school, Kalisuren, Bogor. The methodology used is qualitative. Data collection techniques used are observation, interview and documentation. Technical analysis of data used is data reduction, data presentation and conclusion. The results of this study conclude that: Educational values of humanity applied in Insan Teladan junior high school there was positive for example has a daily and environment around students while still have several factors barrier in applying them. It is purpose which is to produce students not just succeed from the academic side but also from the moral and humanitarian.